The Effect of Uploads on Folkative on the Fulfillment of Information for Z Generation - Darmawan, Nelfina; Safitri, Dini; Putri, K.Y.S.; Sary, Marisa Puspita; Putri, Maulina Larasati; Sutjipto, Vera Wijayanti (Journal of Digital Marketing and Communication, 2024)
A rapid development, especially in the technology industry, led to a big impact on media development. A lot of media companies switched from conventional media to digital media because of fear of being eroded and disability to adapt with the digital advances. not only that, there were also a lot of new online media appearance based on social media, one of which is Folkative. We cannot deny that social media is a new platform which is loved by lots of people, especially Z generation, so the appearance of new online media such as Folkative created a uniqueness of it. Folkative itself is a new online media platform based on Instagram which focused on news, art, culture, and local products, Folkative was called as new media since it was established on 2018. This research aims to determine the effect of uploads on Folkative on the fulfillment of information for Z generation. This research is quantitative research which defines phenomenon with numbers. This research also focused on communication major student at Universitas Negeri Jakarta especially on class of 2020 as the population. This research tests the validity and reliability of data, simple linear regression test to check the effect, and hypothesis test using IBM SPSS (Statistical Product and Service Solutions) version 25. Based on the results of this research, it was determined that there was a positive impact of 15,6%, so it was concluded that there was an effect of uploads on Folkative on the fulfillment of information for Z generation.